Short-term outcomes in early term infants (born at 37 or 38 weeks): a retrospective investigation - Kitamura, Tsubasa; Tabata, Kyosuke; Murano, Yayoi; Yoneoka, Daisuke; Nakazawa, Tomoyuki; Sakamaki, Ken; Shoji, Hiromichi (Frontiers in Pediatrics, 2024)
Introduction Recently, researchers have introduced the concept of ‘early term’ infants, defined as infants born at 37 or 38 weeks of gestation, and their outcome has been discussed. Although the complications experienced by early term are less severe than those in preterm infants, this group accounts for a much larger proportion of newborns, making the assessment of outcomes important in clinical practice. Methods This observational study of term infants born at Tokyo Metropolitan Toshima Hospital aimed to understand the short-term outcomes in early term infants. Data extracted from the medical records were analyzed. Results Among 4,669 eligible participants, 463 (9.9%) were born at 37 weeks and 1,270 (27.2%) were born at 38 weeks. The remaining 2,936 infants were born after 39 weeks of gestation. Logistic regression analysis showed higher odds ratio of hospitalization (1.56, 95% CI: 1.37–1.79, p < 0.05), apnea (2.23, 95%CI: 1.08–4.60, p < 0.05), and hypoglycemia (3.13, 95%CI: 1.95–5.03, p < 0.05) in early term infants. In detail, infants born at 37 weeks of gestational age had higher odds ratio for hospitalization (2.07, 95%CI: 1.68–2.35, p < 0.05) and hypoglycemia (4.11, 95%CI 2.22–7.60, p < 0.05) than infants born at 38 weeks of gestational age (1.40, 95%CI: 1.20–1.62, p < 0.05, and 2.78, 95%CI: 1.66–4.67, p < 0.0 respectively). Discussion This study revealed complicated clinical course in early term infants, and represents one of the largest contributions to understanding the outcomes of early term infants, and could help to determine strategies for elective cesarean section. According to this result, elective cesarean sections would be better planned at 38 weeks of gestational age. Moreover, in clinical practice, it is important to be aware of the complicated clinical course in early term infants.